Reinterpretasi Asbāb Al-Nuzūl bagi Penafsiran Alquran - Irma Riyani; Yeni Huriani (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2017)
Asbāb al-nuzūl are socio-historical events surrounding the revelation of the Qur’an and they are important aspects to understand the meaning of the Qur’an. Unfortunately, in many tafsir that written either in classical or modern exegesis many exegetes seem to ignore the important messages of these socio-historical aspects of the Qur’an. Many exegetes only focus on the texts and produce the textual-doctrinal understanding of the Qur’an that detached from its context. This article based on the claim of universality of the messages of the Qur’an to all human beings across time and space. This article employs interpretative-analysis method to analyze the use of Asbāb al-nuzūl in kitab tafsir – classic and modern - and to seek a new understanding in both: the theory a well as the use of Asbāb al-nuzūl for Qur’anic interpretation. This article shows that the study of Asbāb al-nuzūl should be concerned not only with the specific events of the revelations but also with the spirit of the time when the events occurred in order to understand the basic meaning intended by the texts revealed in various occasions. Therefore, the meaning of the Qur'an should be derived not only from the general meaning of the texts but also from the contexts of the revelations (al-ibrat bi umum al-lafzh ma’a mura’at khusus al-sabab). Interpreting the Qur’an by paying attention to socio-historical approach will lead us to a more dynamic and dialogical interpretation with the cultural contexts without ignoring the ethical principles of the Qur’an.